Multiple Input Single Output DC to DC Converter Control Using Kalman Filter for Microgrid Applications: MISO DC to DC Converter Control using Kalman Filter - Farooq, Waqas; Alvi, Muhammad J.; Izhar, Tahir (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
Renewable energy system (RES) based microgrid applications have grown extensively over the recent years. Owing to power fluctuations in RES, acquiring stable and accurate output voltage at the DC Bus is a major concern in DC microgrid applications. Presently, switching, as well as, prediction of output voltage for RES is quite slow and total harmonic distortion cannot be reduced to a minimal level. Accordingly, this research developed a controller for Multiple Input Single Output (MISO) DC to DC converter and a Kalman filter. Initially, four seriesconnected PV panels were modelled and analysed. A boost converter was used to combine PV panels' output and provide a single output at the DC Bus. Perturb and Observe, a Maximum Power Point Tracking (MPPT) algorithm, was used to retrieve optimal power from modelled RES. Analysis revealed that the output voltage waveform contained harmonics and had a Total Harmonic Distortion (THD) of 27.73 %. Thus, a Kalman filter was modeled and analysed to remove the harmonics. The THD value was consequently reduced to 2.1 %, which is quite within the allowable limit prescribed by IEEE, for the THD of a PV system. Analysis revealed that a stable and accurate output from a PV based RES could be achieved with the proposed scheme, and further THD was also well within limits prescribed by IEEE.